1992
DOI: 10.1172/jci115989
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure of human pancreatic islets to high glucose concentrations in vitro impairs the beta-cell function.

Abstract: The aim of the present study was to clarify whether prolonged in vitro exposure of human pancreatic islets to high glucose concentrations impairs the function of these cells. For this purpose, islets isolated from adult cadaveric organ donors were cultured for seven days in RPMI 1640 medium supplemented with 10% fetal calf serum and containing either 5.6, 11, or 28 mM glucose. There was no glucose-induced decrease in islet DNA content or signs of morphological damage. However, islets cultured at 11 or 28 mM gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
227
1
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(253 citation statements)
references
References 40 publications
22
227
1
3
Order By: Relevance
“…With our model of in-vitro human islets, we showed that beta-cell alterations characteristic of clinical Type 2 diabetes, including loss of GSIS and decrease in insulin content, can be reproduced with either increased glucose or NEFA concentrations. The deleterious effect of high glucose is well established [2,3], but increased NEFA at physiological glucose concentrations were also able to significantly alter GSIS and insulin content. These results are in accordance with previous studies [6,10,33], but argue against the hypothesis that increased glucose is a prerequisite for the deleterious effect of NEFA on betacell function [11,12,13,14].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…With our model of in-vitro human islets, we showed that beta-cell alterations characteristic of clinical Type 2 diabetes, including loss of GSIS and decrease in insulin content, can be reproduced with either increased glucose or NEFA concentrations. The deleterious effect of high glucose is well established [2,3], but increased NEFA at physiological glucose concentrations were also able to significantly alter GSIS and insulin content. These results are in accordance with previous studies [6,10,33], but argue against the hypothesis that increased glucose is a prerequisite for the deleterious effect of NEFA on betacell function [11,12,13,14].…”
Section: Discussionmentioning
confidence: 91%
“…However, whether glucose and NEFA alter beta-cell function synergistically or separately, remains controversial. Some authors have shown that beta-cell failure was induced by increased glucose alone [2,9] or increased NEFA alone [6,10], while others have suggested that excess glucose or NEFA are not deleterious separately, but synergize in causing glucolipotoxicity [11,12,13,14].…”
mentioning
confidence: 99%
“…Other studies in human islets have shown that culture at high glucose for several days leads to downregulation of insulin biosynthesis, possibly secondary to decreased expression of the relevant transcription factors (12). Still other studies have reported decreased glucose metabolism (13). The role of overstimulation versus effects of glucose per se could not, however, be assessed in these experiments.…”
mentioning
confidence: 84%
“…The isolation and culture conditions for human pancreatic islets have been described previously [15]. The islets were subsequently sent by air to Uppsala, where they were cultured in RPMI 1640 medium containing 10% FCS and 5.6 mM glucose.…”
Section: Islet Isolation Culture and Test Agent Treatmentmentioning
confidence: 99%
“…The islets were subsequently sent by air to Uppsala, where they were cultured in RPMI 1640 medium containing 10% FCS and 5.6 mM glucose. We have previously shown that functional preservation in RPMI 1640 medium is optimal at 5.6 mM glucose for human islets [15] and at 11 mM for rodent islets [10,14]. After 5-6 days in culture, groups of human islets were acutely exposed to peroxynitrite (0.2 or 1.0 mM) for 10 min and then functional and survival studies were performed either immediately after (acute) or following a subsequent period of 24 h in culture without the radical (see below).…”
Section: Islet Isolation Culture and Test Agent Treatmentmentioning
confidence: 99%